EXCITATION OF Zn ATOMS TO THE 4snf RYDBERG STATES - Kutsenko, A. S.; Pogrebnyak, N. L.; Dyubko, S. F. (Видавничий дім «Академперіодика», 2015)
A new two-stage scheme of laser excitation of Zn atoms to the 4snf Rydberg states is presented. A modification of the laser-microwave spectrometer of the Institute of Radio Astronomy intended for recording of Rydberg spectra of Zn atoms is described.Key words: Rydberg atom, zinc, laser excitation, spectrometerManuscript submitted 18.06.2014Radio phys. radio astron. 2014, 19(4): REFERENCES1. BIEMONT, E. and GODEFROID, M. A., 1980. Reassessment of the Zinc Solar Abundance. Astron. Astrophys. vol. 84, no. 3, pp. 361–363. 2. SNEDEN, C., GRATTON, R. and CROCKER, D., 1991. Trends in copper and zinc abundances for disk and halo stars. Astron. Astrophys., vol. 246, no. 2, pp. 354–367. 3. GULLBERG, D. and LITZEN, U., 2000. Accurately measured wavelengths of Zn I and Zn II Lines of Astrophysical interest. Physica Scripta, vol. 61, no. 6, pp. 652–656. DOI: https://doi.org/10.1238/Physica.Regular.061a00652 4. MACADAM, K. B., DYUBKO, S. F., EFREMOV, V. A., KUTSENKO, A. S., and POGREBNYAK, N. L., 2012. Microwave spectroscopy of singlet Mg I in L=0–4 Rydberg states. J. Phys. B: At. Mol. Opt. Phys. vol. 45, no. 21, id. 215002. DOI: https://doi.org/10.1088/0953-4075/45/21/215002 5. KUTSENKO, A. S., 2012. Laser-microwave spectroscopy of singlet F-terms of the Mg I atom. Radio Phys. Radio Astron. vol. 3, no. 4, pp. 353–357. 6. SUGAR, J. and MUSGROVE, A., 1995. Energy levels of Zinc, Zn I through Zn XXX. J. Phys. Chem. Ref. Data, vol. 24, no. 6, pp. 1803–1872. DOI: https://doi.org/10.1063/1.555971 7. BROWN, C., TILFORD, S. and GINTER, M., 1975. Absorption spectra of Zni and Cdi in the 1300-1750 Å region. J. Opt. Soc. Am. vol. 65, Is. 12, pp. 1404–1409. 8. ESHKOBILOV, N. B., 2000. Laser spectroscopy of the Rydberg states of atoms group IIB (Zn, Cd, Hg). J. Appl. Spectrosc. vol. 67, Is. 2, pp. 343–345. 9. NADEEM, A., NAWAZ, M., BHATTI, S. A. and BAIG, M. A., 2006. Multi-step laser excitation of the highly excited states of zinc. Opt. Commun., vol. 259, Is. 2, pp. 834–839. DOI: https://doi.org/10.1016/j.optcom.2005.08.075 10. NAWAZ, M., NADEEM, A., BHATTI, S. A. and BAIG, M. A., 2006. Two-step laser excitation of 4snd 3D1,2,3 and 4sns 3S1 states from the 4s4p 3P levels in zinc. J. Phys. B: At. Mol. Opt. Phys. vol. 39, no. 4, pp. 871–881. DOI:https://doi.org/10.1088/0953-4075/39/4/011 11. KOMPITSAS, M., BAHARIS, C. and PAN, Z., 1994. Rydberg states of zinc and measurement of the dipole polarizability of the Zn+ ion. J. Opt. Soc. Am. B, vol. 11, no. 5, pp. 697–702. DOI: https://doi.org/10.1364/JOSAB.11.000697 12. SHAO, Y., FOTAKIS, C. and CHARALAMBIDIS, D., 1993. Multiphoton ionization of Mg in the wavelength region of 300–214 nm. Phys. Rev. A. vol. 48, Is. 5, pp. 3636–3643. 13. MERKT, F., OTERWALDER, A., SEILER, R., SIGNORELL, R., PALM, H., SCMUTZ, H. and GUNZINGER, R., 1998. High Rydberg states of argon: Stark effect and field-ionization properties. J. Phys. B: At. Mol. Opt. Phys. vol. 31, no. 8, pp. 1705–1724.